Fournier's gangrene that initially mimicked pubic cellulitis in an elderly woman administered a Janus kinase inhibitor, methotrexate, and prednisolone for rheumatoid arthritis - Takahiro Shiratori; Naoki Oiso; Kohei Yamauchi; Akira Kawada (Frontiers Media S.A., 2020)
This is the first reported case of FG during administration of a JAK inhibitor. The case appeared to be a less serious manifestation when first examined; however, extremely serious clinical features developed immediately after the withdrawal of TOF.